The Influence Of Medicine Ball Training On Chest Passes Of Basket Ball - 'IZZA, HAFIDZ MIFTAHUL; Runasari, Rellya; Ariesna, Rachmat Dody (AHSANTA JURNAL PENDIDIKAN, 2024)
This study aims to determine the effect of medicine ball training on the results of basketball chest passes in class 9th students at SMP Negeri 3 Tanjung Bintang. This study is a pre-experimental research using the one group pre test-post test design. Sampling was done by random sampling and obtained 28 samples with 12 boys and 16 girls in class 9A. Data collection techniques chest pass test results using the basketball passing test from the AAHPERD Basketball Test. Data analysis used wilcoxon test. The test analysis results obtained p 0.000 < a 0.05 so Ho is rejected and Ha is accepted. It can be concluded that there is an effect of giving medicine ball exercises on the results of basketball chest passes in students. With the right and measurable medicine ball exercise combined with a systematic training program in stages, it will have an influence on the accuracy of the chest pass ability.